Analisis Jaringan Komunikasi Dalam Pengelolaan dan Perencanaan Program Adipura Kota Malang: Studi Jaringan Komunikasi Masyarakat Desa Tamanharjo Dalam Program Adipura Kota Malang - Nafisah Alyfah (Prisani Cendekia Institute, 2023)
This study intends to examine how the communication network process of members of the Malang City Adipura program activities in Tamanharjo Village, by analyzing and knowing the sociogram form or structure of the communication network of the small group. This communication network research is interesting to review again, because of the background of the newly implemented activities. The method in this study uses quantitative descriptive methods. The results of this study are in the form of values managed in the UCINET VI application, where these values are obtained by the results of questionnaires that have been disseminated to respondents who have been selected by purposive sampling. The Adipura activity program implemented by the Malang City Government aims to make the City environment clean and beautiful. Because considering that Malang City is a city whose visitors come from various countries, so it requires management and planning to maintain the City environment.